Significant improvement of a clinical training course in physical examination after basic structural changes in the teaching content and methods - Sonne, Carolin (German Medical Science GMS Publishing House, 2013)
Background: Regular student evaluations at the Technical University Munich indicate the necessity for improvement of the clinical examination course. The aim of this study was to examine if targeted measures to restructure and improve a clinical examination course session lead to a higher level of student satisfaction as well as better self-assessment of the acquired techniques of clinical examination. Methods: At three medical departments of the Technical University Munich during the 2010 summer semester, the quantitative results of 49 student evaluations (ratings 1-6, German scholastic grading system) of the clinical examination course were compared for a course before and a course after structured measures for improvement. These measures included structured teaching instructions, handouts and additional material from the Internet. Results: 47 evaluations were completed before and 34 evaluations after the measures for improvement. The measures named above led to a significant improvement of the evaluative ratings in the following areas: short introduction to the topic of each clinical examination course (from 2.4±1.2 to1.7±1.0; p=0.0020) and to basic measures of hygiene (from 3.8±1.9 to 2.5±1.8; p=0.004), structured demonstration of each clinical examination step (from 2.9±1.5 to 1.8±1.0; p=0.001), sufficient practice of each clinical examination step (from 3.1±1.8 to 2.2±1.4; p=0.030) structured feedback on each clinical examination step (from 3.0±1.4 to 2.3±1.0; p=0.0070), use of handouts (from 5.2±1.4 to 1.8±1.4; p<0.001), advice on additional learning material (from 5.0±1.4 to 3.4±2.0; p<0.001), general learning experience (from 2.4±0.9 to 1.9±0.8; p=0.017), and self-assessment of the acquired techniques of clinical examination (from 3.5±1.3 to 2.5±1.1; p<0.01). Conclusion: Structured changes led to significant improvement in the evaluative ratings of a clinical examination course session concerning preparation of the tutors, structure of the course, and confidence in performing physical examinations.